Las metáforas comestibles en los rituales mexicanos - Danièle Dehouve (Les Cahiers ALHIM)
This article introduces a method of semantic decoding of certain dishes cooked as part of the rituals of the Aztecs at the time of Spanish Conquest and of several contemporary Indian groups. Starting from the idea that, in a ritual nothing is unpredictable and everything has a sense, it introduces a reflection about the categories of metaphor and metonymy conceived as two founding mechanisms of the human mind, at the same time distinct and closely linked, which express themselves in a verbal and material manner. Difrasismos, often considered to be linguistic techniques typical of ritual mesoamerican speeches, are considered here to be particular cases of « definition by extension », which forms « metonymical series ». The ritual dishes are analysed as material and eatable difrasismos which first of all represent a metonymical technique, and constitute the basis of metaphors.